The THE EFFECT OF THE NUMBERED HEAD TOGETHER TYPE COOPERATIVE LEARNING MODEL USED BY DIORAMA COMPLETED WITH CROSS PUZZLE LKPD ON THE LEARNING OUTCOMES OF STUDENTS OF MUHAMMADIYAH WAINGAPU JUNIOR HIGH SCHOOL: PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER BERBANTUAN DIORAMA DILENGKAPI LKPD TEKA TEKI SILANG TERHADAP HASIL BELAJAR SISWA SMP MUHAMMADIYAH WAINGAPU - Munggul, Santri May; Bano, Vidriana Oktoviana; Rosalia Ndapa Huda, Marleni (Jurnal Biogenerasi, 2025)
This study aims to determine whether the (NHT) learning approach combined with diorama media displaying LKPD crossword puzzles can affect the learning outcomes of seventh grade students at Muhammadiyah Waingapu Middle School. This type of research is experimental research. It consists of two classes: the experimental class and the control class. The stages of the research are: preparation, implementation, and completion. The sample for this study consisted of 18 students of class VII A, which is the experimental class, and 16 students of class VII B, which is the control class. The data collection techniques and instruments used were tests. The data analysis techniques used were validity and reliability tests, descriptive analysis, normality and homogeneity tests, hypothesis testing, namely paired sample t-tests using SPSS version 31. The results of the study can be seen from the comparison of the average value of the control class 49.06 (pretest), 59.06 (posttest) and the experimental class average value obtained 57.78 (pretest), 89.44 (posttest). The results of hypothesis testing using the dependent sample t test which has a Sig value (2-tailed) of 0.000 means that the value is <0.05 so that H0 is rejected and H1 is accepted. It can be concluded that the numbered head together learning model assisted by diorama media equipped with LKPD Crossword Puzzles has a significant effect on the learning outcomes of class VII A students which is an experimental class at SMP Muhammadiyah Waingapu.